Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.17061/phrp3152128
|View full text |Cite
|
Sign up to set email alerts
|

Older adults’ perceptions of current and future hearing healthcare services in Australia, England, US and Canada

Abstract: Recent and significant changes in policy and service delivery approaches, using over-the-counter models, have been developed to specifically address cost and accessibility of hearing healthcare (HHC) services • This qualitative study demonstrates that, although cost remains a key challenge, long-standing issues of stigma and trust in the HHC system -originally identified about 30 years ago -remain despite significant technological advances and generational change • Such barriers may remain an impediment to HHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Participants frequently noted that general practitioners did not discuss hearing loss or refer for testing, mirroring studies revealing disparities in specialty referrals for patients seen in primary care, such as significantly delayed or disparate referrals for Hispanic patients for chronic renal failure (Ifudu et al 1999), coronary artery or congestive heart failure (Cook et al 2009), mental healthcare for the treatment of depression and anxiety (Laomasino et al 2011), and treatment for rheumatoid arthritis (Mariam et al 2020). A lack of referral for a hearing test expressed by participants in the present study also aligns with the findings of McKee et al (2018), Carlson et al (2019), andMcMahon et al (2021), whose qualitative study results revealed that primary care providers did not discuss or minimized hearing loss, screenings, or hearing devices at appointments. However, these studies included few, if any, Hispanic/Latino adults, and is difficult to draw conclusions regarding whether Hispanic/ Latino background was a contributing factor.…”
Section: Structural Clinical and Organizational Barriers To Caresupporting
confidence: 85%
See 1 more Smart Citation
“…Participants frequently noted that general practitioners did not discuss hearing loss or refer for testing, mirroring studies revealing disparities in specialty referrals for patients seen in primary care, such as significantly delayed or disparate referrals for Hispanic patients for chronic renal failure (Ifudu et al 1999), coronary artery or congestive heart failure (Cook et al 2009), mental healthcare for the treatment of depression and anxiety (Laomasino et al 2011), and treatment for rheumatoid arthritis (Mariam et al 2020). A lack of referral for a hearing test expressed by participants in the present study also aligns with the findings of McKee et al (2018), Carlson et al (2019), andMcMahon et al (2021), whose qualitative study results revealed that primary care providers did not discuss or minimized hearing loss, screenings, or hearing devices at appointments. However, these studies included few, if any, Hispanic/Latino adults, and is difficult to draw conclusions regarding whether Hispanic/ Latino background was a contributing factor.…”
Section: Structural Clinical and Organizational Barriers To Caresupporting
confidence: 85%
“…Participant discussions revealed an interesting paradox of wanting physical appearance to remain youthful and vibrant for as long as possible, while also embracing and accepting the aging process and the natural sensory losses that occur among older relatives. Those with hearing loss described frustrations when communicating in group situations or other adverse listening environments, a well-documented problem that was also shared by participants in previous qualitative studies investigating attitudes and beliefs of hearing loss (McKee et al 2018;Carlson et al 2019;McMahon et al 2021), including those focused on Korean Americans (Choi et al 2018).…”
Section: Hearing Loss and Hhc Lived Experiencesmentioning
confidence: 85%
“…É dependente de fatores como boa habilidade manual, grau de encaixe/conforto dos moldes auriculares, ruídos ambientais, conhecimento dos familiares sobre deficiência auditiva e apoio social, disponibilidade de atendimento dos serviços de saúde auditiva e de assistência técnica [17][18][19] . O apoio familiar é fundamental na efetividade do processo de reabilitação, pois colaboram na compreensão de instruções, aumentam o sentimento de segurança do usuário, facilitam o reconhecimento de suas dificuldades e o acesso a serviços de saúde 22,23 . Em contrapartida, a descontinuidade dos serviços de saúde auditiva durante a pandemia dificultou o acesso à compra de pilhas, reparo de dispositivos quebrados, confecção de novos moldes auriculares e reprogramação de dispositivos [19][20][21] , com consequente diminuição no tempo de uso diário dos DAES, problemas relacionados à audição (infecções, tontura e zumbido) e dificuldades de comunicação com familiares 19 .…”
Section: Conclusãounclassified
“…A integralidade do indivíduo com perda auditiva deve ser considerada durante os atendimentos em saúde, visto que doenças crônicas podem ser fatores de risco para a perda auditiva 22 . Indivíduos com problemas auditivos frequentemente relatam ter saúde geral ruim, maior número de comorbidades crônicas e de limitações funcionais 15 .…”
Section: Conclusãounclassified
“…The hearing care culture is becoming more receptive to consumer demands, experiences, and decisions over where to receive their hearing care. 11 As a result of this new dynamic, hearing care must recognize that it is now more important than ever to be adaptable and responsive to consumers.…”
Section: Tablementioning
confidence: 99%